Primary School Teachers' Knowledge on Tooth Avulsion - Ivan Salarić; Daniela Tikvica Medojević; Ksenija Baždarić; Josipa Kern; Ante Miličević; Petar Đanić; Josip Biočić; Darko Macan (University of Zagreb. School of Dental Medicine, 2021)
Objective: Permanent teeth trauma is most frequent in children aged 7-9 years, and the primary school teachers (PSTs) are often the first to notice it. The aim of this study was to evaluate the competence in tooth avulsion clinical issues and knowledge on dental trauma of PSTs, as they can occasionally take on the role of school nurses. Material and Methods: Questionnaires were handed to 312 PSTs from 24 randomly selected primary schools in Zagreb, Croatia. An algorithm was designed for PST competence assessment. Results: Response rate amounted to 81.37% (N=255). Only 3.14% (N=8) of the PSTs would replant the permanent tooth properly and only 43.92% of them (N=112) would immediately take the child to a doctor of dental medicine. Dry tissue, as a transport medium for an avulsed tooth, was chosen by 50.20% (N=128) of the respondents. Altogether, 4.71% (N=12) of PSTs were graded as competent in case of child's tooth avulsion. Conclusion: These results provided significant implications for school health, showed the educators' serious lack of knowledge in cases of dental trauma and stressed a need for continuous education of PSTs on the topic.